Deposition of satellited Al-TiC powders for coating applications - Al-hamdani, Kamaal (2019)
Metal matrix composite (MMC) coatings have good wear resistance, given the combined ductility of the metal matrix and high hardness and strength of the ceramic reinforcements. Surface modification by coating deposition is an important approach for improving the functional surface region of materials without replacing the entire component, which is also a cost-effective approach for extension the component working life.